Composition for preparing multi-layer coated gel particles, multi-layer coated gel particles and preparation method and application of multi-layer coated gel particles
By forming a multi-layer coating on the surface of frozen glue particles, the glue formation process is delayed, and the existing frozen glue type regulators are solved, and the stability and deep sealing effect of frozen glue particles under high temperature and high salt conditions are achieved.
Patent Information
- Application Number
- CN202510320498.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-06-24
- Estimated Expiration
- 2045-03-18
AI Technical Summary
The existing high-temperature, high-salt joint hole type oil and gas reservoir frozen glue-type regulator cannot be injected deep due to the rapid glue-forming speed, and the glue-forming liquid is diluted by formation water and cannot be sealed deep.
Multi-layer coating frozen glue particles are used to form a first layer of coating and a second layer of coating on the surface of the glue forming liquid particles, so as to delay the glue forming process and ensure that the particles can be effectively sealed after moving deep.
The stability and sealing strength of frozen rubber particles under high temperature and high salt conditions are achieved, deep migration and effective sealing are ensured, and the development efficiency of high-temperature, high-salt joint hole oil and gas reservoirs is improved.
Smart Images

Figure CN120192760A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of oilfield chemical profile control and water plugging, and specifically relates to a composition for preparing multi-layer coated gel particles, the multi-layer coated gel particles, a preparation method thereof, and an application thereof. Background Art
[0002] Unconventional oil and gas resources are an important front for controlling water production and increasing oil production in China to protect national energy security. With the development of unconventional oil and gas resources in China, the exploitation technology of deep-seated fracture-cavity type oil and gas reservoirs has become increasingly perfect. Fracture-cavity type carbonate rock oil reservoirs (fracture-cavity type oil reservoirs) are mainly distributed in the Tarim Basin, among which the total proven petroleum geological reserves of Tahe Oilfield, Lungu Oilfield, Halahatang Oilfield, Fuman Oilfield, Shunbei Oil and Gas Field, etc. have exceeded 20.0×10 8 t, and the annual output reaches 700×10 4 t, which are important strategic replacement resources. In the current development technology of high-temperature and high-salt fracture-cavity type oil and gas reservoirs, water injection exploitation is the most widely used. However, the extreme heterogeneity of fracture-cavity reservoirs leads to water channeling, which has become an important factor affecting the development of high-temperature and high-salt fracture-cavity type oil and gas reservoirs. Different from traditional pore-type oil reservoirs, many wells in fracture-cavity type oil reservoirs will be shut in due to rapid violent water flooding (water cut approaching 100%) after water injection. The regulation effect in the near-well area is gradually declining. The regulation of flow heterogeneity in the deep area of fracture-cavity reservoirs has become an effective way to assist the development of high-temperature and high-salt fracture-cavity type oil and gas reservoirs, and the core of which is the research and development of regulators. Gel-type regulators have stable gel-forming effects, controllable gel properties, temperature and salt resistance, and simple preparation, and have become widely used regulators. However, the high-viscosity gel-forming liquid and short gel-forming speed make it difficult for the gel to meet the requirements of deep flow regulation.
[0003] CN116333704A discloses a gel system that rapidly forms a gel under high-temperature and high-salt conditions and a preparation method thereof. For this gel system, calculated by weight percentage, the raw materials include: 2-4% phenolic prepolymer, 0.1-0.2% polyethylene glycol, 0.6-1% polymer, and a brine system. The polymer is an acrylamide / 2-acrylamide-2-methylpropanesulfonic acid copolymer with a molecular weight of 8 million; this gel system can rapidly form a gel in a short time, solving the problem that the gel in high-temperature and high-salt fracture-cavity oil reservoirs may be diluted by formation water, resulting in poor gel strength or no gel formation. It is suitable for oil reservoirs with a formation temperature of <150°C and a salinity >20×10 4 mg / L, but the gel-forming time of this gel is 1-1.5 h, and the gel-forming speed is too fast to be transported deep.
[0004] CN118772447A discloses an elastic gel particle and a preparation method thereof. The gel particle is obtained by granulating a gel prepared from silicate, a cross-linking agent, sulfonated phenolic resin, and polyvinyl alcohol under the action of an acid catalyst. The particle size is 1×10 1 to 3×10 6nm, which can be aged for 90 days at 130 °C and a salinity of 214812.46 mg / L. After 5 times of extrusion, the deformation recovery rate is 60 to 87%, the dehydration rate is 15% to 30%, and the volume shrinkage rate is 29% to 45%. However, the gel particles do not consider the particle coalescence rate of particles under high temperature and high salinity, and it is impossible to determine their deep migration ability.
[0005] CN113897189A discloses a gel system and its application suitable for profile control in high-temperature and high-salinity fracture-vuggy reservoirs. The system is composed of AM / AMPS copolymer, non-ionic polyacrylamide, hexamethylenetetramine, hydroquinone, and the balance of water. A heat-resistant and salt-resistant AM / AMPS copolymer and a common non-ionic polyacrylamide are compounded as the gelling agent of the gel system. At a temperature as high as 130 °C and a formation water salinity as high as 220000 mg / L, while ensuring the stability and strength of the gel, the cross-linking reaction rate is accelerated, and the adverse effect of formation water dilution on the gel is reduced. However, the effect of avoiding formation water dilution by this method is limited, and it will affect the effect of deep injection.
[0006] Therefore, it is urgent to develop a gel system that can adjust the flow deeply to meet the regulation of reservoir heterogeneity in high-temperature and high-salinity fracture-vuggy oil and gas reservoirs. Summary of the Invention
[0007] The purpose of the present invention is to overcome the problems of the existing gel-type regulators for high-temperature and high-salinity fracture-vuggy oil and gas reservoirs, such as the gelation speed being too fast to be injected deeply and the gel-forming liquid being diluted by formation water and unable to plug deeply. The present invention provides a composition for preparing multi-layer coated gel particles, the multi-layer coated gel particles, and their preparation methods and applications. When the multi-layer coated gel particles are injected into the formation, the outer two-layer coating gradually degrades, exposing the inner one-layer coating. The gel-forming liquid particles agglomerate with each other to form aggregates, and plugging is formed deep in the formation.
[0008] To achieve the above purpose, the first aspect of the present invention provides a multi-layer coated gel particle, wherein the multi-layer coated gel particle includes one-layer coated gel-forming liquid particles and a two-layer coating covering the outer surface of the one-layer coated gel-forming liquid particles; the two-layer coating is formed by the one-layer coated gel-forming liquid particles and a dichloromethane solution containing a two-layer coating agent and a dispersing aid, wherein the two-layer coating agent is polylactic acid and the dispersing aid is polyethylene glycol.
[0009] The second aspect of the present invention provides a composition for preparing multi-layer coated gel particles, wherein the composition includes a gel-forming liquid, a calcium ion-containing salt solution, and a dichloromethane solution containing a two-layer coating agent and a dispersing aid, which are stored independently;
[0010] wherein the gel-forming liquid includes one or more of preparation water, polyacrylamide, phenolic resin, and a one-layer coating agent;
[0011] Among them, the first-layer film coating agent is one or more of fructose, carrageenan, sodium alginate, xanthan gum, carboxymethyl cellulose, sodium carboxymethyl starch, chitosan, sodium polyacrylate, and polyacrylic acid;
[0012] Among them, the second-layer film coating agent is polylactic acid;
[0013] Among them, the dispersant aid is polyethylene glycol.
[0014] The third aspect of the present invention provides a method for preparing multi-layer film-coated gel particles using the composition described in claim 4 or 5, wherein the method includes:
[0015] (1) Under stirring conditions, first mix the liquid preparation water and polyacrylamide to obtain a polymer solution;
[0016] (2) Second mix the polymer solution and phenolic resin to obtain a gel-forming liquid;
[0017] (3) Contact the gel-forming liquid with the first-layer film coating agent for cross-linking reaction to obtain a strengthened gel-forming liquid;
[0018] (4) Drop the strengthened gel-forming liquid into a salt solution containing calcium ions to obtain first-layer film-coated gel-forming liquid particles;
[0019] (5) Put the first-layer film-coated gel-forming liquid particles into a dichloromethane solution containing the second-layer film coating agent and the dispersant aid to obtain multi-layer film-coated gel particles.
[0020] The fourth aspect of the present invention provides multi-layer film-coated gel particles prepared by the method described above.
[0021] The fifth aspect of the present invention provides an application of the multi-layer film-coated gel particles described above as a plugging agent in high-temperature and high-salt fracture-vuggy oil and gas reservoirs.
[0022] Through the above technical solutions, the present invention has the following beneficial effects:
[0023] (1) The multi-layer film-coated gel particles of the present invention have good dispersion effect, stable gel-forming performance, high plugging strength after particle coalescence, and strong long-term thermal stability.
[0024] (2) The components in the multi-layer film-coated gel particles of the present invention have good compatibility, the preparation of the gel-forming liquid is simple, and the presence of the first-layer film coating agent, the second-layer film coating agent, and the dilution-resistant aid does not affect the gel-forming effect.
[0025] (3) The raw materials of the components in the multi-layer film-coated gel particle composition of the present invention have wide sources, and are suitable for industrial production and on-site large-scale preparation operations.
[0026] (4) The hydrophilic groups of the dispersant polyethylene glycol used in the present invention, namely the ether bond (-O-) and the connected hydroxyl group (-OH), endow the surface of the multi-layer coated gel particles of the present invention with certain hydrophilicity, enabling them to maintain good dispersion in the aqueous phase.
[0027] (5) The methyl group (-CH3) in the two-layer coating agent polylactic acid used in the present invention makes the coating outside the multi-layer coated gel particles of the present invention dense and hydrophobic, which can avoid the dilution of the gel-forming liquid by formation water.
[0028] (6) When the multi-layer coated gel particles of the present invention are injected into the formation, the outer two-layer coating gradually degrades, exposing the inner one-layer coating. The gel-forming liquid particles agglomerate with each other to form aggregates, forming a plugging in the deep part of the formation. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is a schematic diagram for the preparation of the multi-layer coated gel particles of the present invention;
[0030] Figure 2 is a schematic diagram for the deep migration and plugging of the multi-layer coated gel particles of the present invention;
[0031] Figure 3 is a macroscopic diagram of the multi-layer coated gel particles prepared in Example 1 of the present invention;
[0032] Figure 4 is a macroscopic diagram of the multi-layer coated gel particles prepared in Example 1 of the present invention after coalescence under high temperature, high salt and formation water conditions;
[0033] Figure 5 is an SEM photograph of the microscopic network structure of the multi-layer coated gel particles prepared in Example 2 of the present invention after coalescence under high temperature, high salt and formation water conditions;
[0034] Figure 6 is a macroscopic diagram of the ordinary gel prepared in Comparative Example 1 before and after gel formation under high temperature, high salt and formation water conditions. DETAILED DESCRIPTION OF THE INVENTION
[0035] In the ranges disclosed herein, the endpoints and any values are not limited to the exact ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, between the endpoint values of each range, between the endpoint values of each range and individual point values, and between individual point values, they can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein.
[0036] As described above, the first aspect of the present invention provides a multi-layer coated gel particle, wherein the multi-layer coated gel particle includes a layer of coated gel-forming liquid particles and a second layer of coating covering the outer surface of the layer of coated gel-forming liquid particles; the second layer of coating is formed from the layer of coated gel-forming liquid particles and a dichloromethane solution containing a second layer coating agent and a co-dispersant, wherein the second layer coating agent is polylactic acid and the co-dispersant is polyethylene glycol.
[0037] The inventors of the present invention have found that: a strengthened gel-forming liquid formed from polyacrylamide, phenolic resin and a first layer coating agent is coated with a first layer of coating, and the first layer of coating is a dense viscoelastic protective film formed from the first layer coating agent and calcium ions, which can isolate water and initially form a layer of coated gel-forming liquid particles; further, a second layer of coating is coated on the outer surface of the layer of coated gel-forming liquid particles, and the second layer of coating can adhere to the surface of the first layer coating agent and isolate water by virtue of its own hydrophobicity to form gel-forming liquid particles that completely isolate formation water; the co-dispersant can penetrate into the second layer coating agent to improve the hydrophilicity of the particles, increase the surface negative charge, and form water-phase dispersed dilution-resistant gel-forming liquid particles; the above dilution-resistant gel-forming liquid particles form a gel inside at high temperature and high salinity, and the outer coating gradually degrades, exposing the internal gel particles, and the particles adhere to each other to form a plugging in the deep formation.
[0038] According to the present invention, the first layer coating agent is selected from one or more of fructose, carrageenan, sodium alginate, xanthan gum, carboxymethyl cellulose, sodium carboxymethyl starch, chitosan, sodium polyacrylate, and polyacrylic acid; preferably, the first layer coating agent is selected from one or more of fructose, carrageenan, sodium alginate, xanthan gum, and sodium polyacrylate.
[0039] According to the present invention, the outer surface of the layer of coated gel-forming liquid particles is formed from the first layer coating agent and calcium ions, and the inside of the layer of coated gel-forming liquid particles is formed from polyacrylamide, phenolic resin and the first layer coating agent.
[0040] According to the present invention, the thickness of the first layer of coating is 50 - 500 μm, preferably 60 - 500 μm.
[0041] According to the present invention, the thickness of the second layer of coating is 10 - 50 μm, preferably 18 - 42 μm.
[0042] According to the present invention, the average particle size of the multi-layer coated gel particles is 0.5 mm - 10 cm.
[0043] According to the present invention, the polyacrylamide is an AM / AMPS copolymer, wherein AM is water-soluble acrylamide (AM), and AMPS is sodium 2-acrylamido-2-methylpropanesulfonate; and based on the total weight of the AM / AMPS copolymer, the content of AM is 60-70% by weight, and the content of AMPS is 30-40% by weight.
[0044] According to the present invention, the relative molecular weight of the AM / AMPS copolymer is 5 million - 12 million, preferably 8 million - 9 million.
[0045] According to the present invention, the degree of hydrolysis of the AM / AMPS copolymer is 1-10%, preferably 1%-3%.
[0046] According to the present invention, the phenolic resin crosslinking agent is selected from one or more of phenol-type phenolic resin, hydroquinone-type phenolic resin, and resorcinol-type phenolic resin.
[0047] The second aspect of the present invention provides a composition for preparing multi-layer coated gel particles, wherein the composition includes a gelling solution, a calcium ion-containing salt solution, and a dichloromethane solution containing a two-layer coating agent and a dispersing aid, which are stored independently;
[0048] Among them, the gelling solution includes one or more of dispensing water, polyacrylamide, phenolic resin, and a one-layer coating agent;
[0049] Among them, the one-layer coating agent is one or more of fructose, carrageenan, sodium alginate, xanthan gum, carboxymethyl cellulose, sodium carboxymethyl starch, chitosan, sodium polyacrylate, and polyacrylic acid;
[0050] Among them, the two-layer coating agent is polylactic acid;
[0051] Among them, the dispersing aid is polyethylene glycol.
[0052] According to the present invention, the calcium ion-containing salt solution is one or more of calcium chloride, calcium bicarbonate, and calcium hydroxide, preferably calcium chloride; in the present invention, the concentration of calcium ions in the calcium ion-containing salt solution is 0.5-2%;
[0053] According to the present invention, based on the total weight of the gelling solution, the content of the polyacrylamide is 0.3-1.5% by weight; the content of the phenolic resin crosslinking agent is 0.4-1.2% by weight, the content of the one-layer coating agent is 0.2-5% by weight, and the balance is dispensing water; preferably, based on the total weight of the gelling solution, the content of the polyacrylamide is 0.5-1.2% by weight; the content of the phenolic resin crosslinking agent is 0.6-1.0% by weight, the content of the one-layer coating agent is 0.3-0.6% by weight, and the balance is dispensing water.
[0054] According to the present invention, the concentration of the second-layer film coating agent is 5-30%, the concentration of the dispersant aid is 0.1-0.6%, and the balance is methylene chloride; preferably, the concentration of the second-layer film coating agent is 10%-20%, and the concentration of the dispersant aid is 0.2-0.3%, and the balance is methylene chloride.
[0055] The third aspect of the present invention provides a method for preparing multi-layer coated gel particles using the aforementioned composition, wherein the method includes:
[0056] (1) Under stirring conditions, first mix the formulated water and polyacrylamide to obtain a polymer solution;
[0057] (2) Second mix the polymer solution and phenolic resin to obtain a gelling solution;
[0058] (3) Contact the gelling solution with a first-layer film coating agent for a cross-linking reaction to obtain a strengthened gelling solution;
[0059] (4) Drop the strengthened gelling solution into a salt solution containing calcium ions to obtain first-layer coated gelling solution particles;
[0060] (5) Place the first-layer coated gelling solution particles into a methylene chloride solution containing a second-layer film coating agent and a dispersant aid to obtain multi-layer coated gel particles.
[0061] According to the present invention, the conditions for the first mixing include: the temperature is 20±5°C, the time is 60-90 min, preferably 50-60 min;
[0062] According to the present invention, the conditions for the second mixing include: the temperature is 20±5°C, the time is 10-20 min, preferably 10-15 min.
[0063] According to the present invention, in step (3), calcium ions and the first-layer film coating agent undergo a cross-linking reaction, wherein the conditions for the cross-linking reaction include: the temperature is 20±5°C, the time is 20-60 min, preferably 30-50 min.
[0064] The fourth aspect of the present invention provides multi-layer coated gel particles prepared by the aforementioned method.
[0065] The fifth aspect of the present invention provides an application of the aforementioned multi-layer coated gel particles as a plugging agent in high-temperature and high-salt fracture-vuggy oil and gas reservoirs.
[0066] According to the present invention, the conditions of the high-temperature and high-salinity fracture-vug type oil and gas reservoir include: temperature ≥ 110 °C, salinity ≥ 200,000 mg / L, calcium and magnesium ions ≥ 5,000 mg / L; preferably, the temperature is 110 - 150 °C, the salinity is 200,000 mg / L - 300,000 mg / L, and the content of calcium and magnesium ions is 5,000 mg / L - 15,000 mg / L.
[0067] According to the present invention, the weight ratio of the amount of the multi-layer coated gel particles to the formation water is 1:(1 - 9), preferably 1:(1 - 4).
[0068] According to the present invention, the multi-layer coated gel particles coalesce to form aggregates after aging for 48 - 96 h, preferably, the multi-layer coated gel particles coalesce to form aggregates after aging for 48 - 72 h.
[0069] The present invention will be described in detail below through examples.
[0070] In the following examples and comparative examples:
[0071] The strength parameter of the coalesced gel particle aggregate is measured by the elastic test method of a rheometer;
[0072] The core plugging rate parameter is measured by the high-temperature and high-salinity core displacement experiment method;
[0073] The SEM is purchased from Hitachi, and the model is Hitachi S-4800;
[0074] The raw material of the AM / AMPS copolymer is a commercially available product of Nuoer Biotechnology Co., Ltd.;
[0075] The raw materials of the phenol type, hydroquinone type, and catechol type phenolic resin cross-linking agents are commercially available products of Lifeng Chemical New Materials Co., Ltd.
[0076] Example 1
[0077] This example is to illustrate the preparation of multi-layer coated gel particles and their application using the composition for preparing multi-layer coated gel particles.
[0078] The composition for preparing multi-layer coated gel particles includes: a gel-forming solution, a calcium ion salt solution, and a dichloromethane solution containing a two-layer coating agent (polylactic acid) and a dispersing aid (polyethylene glycol); wherein, the gel-forming solution includes preparation water, polyacrylamide, phenolic resin (hydroquinone type phenolic resin), and a one-layer coating agent (carrageenan).
[0079] Among them, the relative molecular mass of polyacrylamide (AM / AMPS copolymer) is 10 million, the hydrolysis degree is 3%, the content of AM is 60% by weight, and the content of AMPS is 40% by weight;
[0080] Among them, based on the total weight of the gelling solution, the content of polyacrylamide is 1.0%; the content of the hydroquinone-type phenolic resin crosslinking agent is 0.6%; the content of the first-layer coating agent carrageenan is 0.3%; the balance is the preparation water with a content of 98.1%, and the sum of the total contents of each component is 100%.
[0081] Among them, the calcium ion salt solution is calcium chloride (CaCl2), and the concentration of calcium ions in the calcium ion-containing salt solution is 1%;
[0082] Among them, the concentration of the second-layer coating agent polylactic acid is 20%, the concentration of polyethylene glycol is 0.3%, and the balance is dichloromethane with a concentration of 79.7%.
[0083] The method for preparing multi-layer coated gel particles using the above composition includes:
[0084] (1) At room temperature (20 ± 5 °C), add 0.8 g of AM / AMPS copolymer to clear water at a stirring rate of 600 revolutions per minute for the first mixing, and stir for 60 minutes to obtain a polymer solution;
[0085] (2) While stirring, add 0.6 g of the hydroquinone-type phenolic resin crosslinking agent for the second mixing, and stir for 10 minutes to obtain a gelling solution;
[0086] (3) While stirring, slowly add 0.3 g of the first-layer coating agent carrageenan for crosslinking reaction, and stir for 30 minutes until it is fully dissolved to obtain a strengthened gelling solution;
[0087] (4) Then, drop the strengthened gelling solution into a 990 g aqueous solution containing 10 g of CaCl2 to obtain first-layer coated gelling solution particles;
[0088] (5) Add the first-layer coated gelling solution particles to a 797 g dichloromethane solution containing 200 g of polylactic acid and 3 g of polyethylene glycol, and stir at a stirring rate of 600 revolutions per minute for 60 minutes, and filter to obtain multi-layer coated gel particles.
[0089] In addition, the prepared multi-layer coated gel particles were characterized, and the results are shown in Table 1.
[0090] In addition, 50 g of multi-layer coated gel particles were placed in 50 g of formation water with a salinity of 220,000 mg / L (10,000 mg / L of Ca 2+ 、Mg 2+ divalent salt ions, and the rest is NaCl), sealed in a pressure-resistant bottle, and after aging at 140 °C for 48 h, the particles coalesced to form large-scale gel particle aggregates. The strength of the gel particle aggregates is 9.6 Pa.
[0091] Figure 1It is a schematic diagram for the preparation of the multi-layer coated gel particles of the present invention. From Figure 1 it can be seen that: First, taking advantage of the characteristic that a layer of coating agent can quickly crosslink with calcium ions, a coating is formed on the surface of the gel-forming liquid, and the gel-forming liquid particles with a preliminary shape are initially formed. Then, a second-layer coating with a dense surface coating is formed by the hydrogen bond and hydrophobic interaction between the second-layer coating agent and the first-layer coating. Among them, SA is the calcium-sensitive polymer of the first-layer coating agent, and PLA is the polylactic acid of the second-layer coating agent, forming multi-layer coated gel particles. The first-layer coating and the second-layer coating adhere to each other by hydrogen bond and hydrophobic interaction to prevent desorption. The gel particles are water-based dispersed and have the characteristics of low viscosity, controllable particle size, high-temperature stability, and dense film resistance to dilution.
[0092] Figure 2 It is a schematic diagram for the deep migration and plugging of the multi-layer coated gel particles of the present invention. From Figure 2 it can be seen that: In the first stage, after the water-based dispersed gel-forming liquid particles are injected into the formation, they remain dispersed in the near-well area and are injected dispersedly near the well, continuously migrating deep into the formation; in the second stage, under the action of high temperature, the gel-forming liquid gels, and a gel is formed inside the coating. However, due to the dispersion effect of the second-layer film, the particles still remain in a mutually dispersed state; in the third stage, after migrating to the deep part of the formation, the coating degrades (the interfacial film degrades) and the internal gel particles are exposed, and the particles agglomerate with each other to form large-scale gel particle aggregates, which coalesce and plug in the deep part to form an effective plugging. In addition, it should be noted that for the convenience of reading the figure more clearly, the water-based dispersed gel-forming liquid particles injected into the formation rock wall in the first stage are enlarged, and the corresponding enlarged diagram is used to represent; the gel-forming of the gel-forming liquid and the gel formed inside the coating in the second stage are enlarged, and the corresponding enlarged diagram is used to represent; in the third stage, the internal gel particles exposed after the coating degrades (the interfacial film degrades) are enlarged, and the corresponding enlarged diagram is used to represent.
[0093] Figure 3 It is a macroscopic schematic diagram of the multi-layer coated gel particles prepared in Example 1 of the present invention. From Figure 3 it can be seen that: The multi-layer coated gel particles prepared in Example 1 of the present invention have good dispersibility in formation water, which is beneficial for continuous and stable injection.
[0094] Figure 4 It is a macroscopic diagram of the multi-layer coated gel particles prepared in Example 1 of the present invention after coalescence under high temperature, high salt and formation water conditions. From Figure 4 it can be seen that: After high-temperature aging, the coating of the multi-layer coated gel particles prepared in Example 1 of the present invention degrades, exposing the internal gel particles, and the particles agglomerate with each other to form large-scale gel particle aggregates; the gel particle aggregates have a dense network structure and can effectively plug the cracks.
[0095] Figure 5 It is an SEM photograph of the microscopic network structure of the multi-layer coated gel particles prepared in Example 2 of the present invention after coalescence under high temperature, high salt and formation water conditions. FromFigure 5 It can be seen that the aggregates formed after coalescence of the multi-layer coated gel particles prepared in Example 2 of the present invention under high temperature, high salt and formation water conditions have a dense network structure and can effectively plug the fractures;
[0096] Example 2
[0097] This example is to illustrate the preparation of multi-layer coated gel particles and their applications using the composition for preparing multi-layer coated gel particles.
[0098] The composition for preparing multi-layer coated gel particles includes: a gelling solution, a calcium ion salt solution, and a dichloromethane solution containing a two-layer coating agent (polylactic acid) and a dispersing aid (polyethylene glycol); wherein, the gelling solution includes prepared water, polyacrylamide, phenolic resin (catechol-type phenolic resin), and a one-layer coating agent (sodium alginate).
[0099] Among them, the relative molecular mass of polyacrylamide (AM / AMPS copolymer) is 8 million, the hydrolysis degree is 2.4%, the content of AM is 65% by weight, and the content of AMPS is 35% by weight;
[0100] Among them, based on the total weight of the gelling solution, the content of polyacrylamide is 1.2%; the content of the catechol-type phenolic resin crosslinking agent is 0.7%; the content of the one-layer coating agent sodium alginate is 0.2%; the balance is prepared water, with a content of 97.9%, and the total content of each component is 100%.
[0101] Among them, the calcium ion salt solution is calcium chloride (CaCl2), and the concentration of calcium ions in the calcium ion-containing salt solution is 1%;
[0102] Among them, the concentration of the two-layer coating agent polylactic acid is 20%, the concentration of polyethylene glycol is 0.3%, the balance is dichloromethane, and the concentration of dichloromethane is 79.7%.
[0103] The method for preparing multi-layer coated gel particles using the above composition includes:
[0104] (1) At room temperature (20 ± 5 °C), add 1.2 g of AM / AMPS copolymer to clear water at a stirring rate of 600 revolutions per minute and stir for 60 minutes to obtain a polymer solution;
[0105] (2) While stirring, add 0.7 g of the catechol-type phenolic resin crosslinking agent and stir for 10 minutes to obtain a gelling solution;
[0106] (3) While stirring, slowly add 0.2 g of the one-layer coating agent sodium alginate and stir for 30 minutes until it is fully dissolved to obtain a strengthened gelling solution;
[0107] (4) Then, the strengthened gelling solution droplets are added into 990 g of an aqueous solution containing 10 g of CaCl₂ to obtain a layer of film-coated gelling solution particles.
[0108] (5) The layer of film-coated gelling solution particles is added into 797 g of a dichloromethane solution containing 200 g of polylactic acid and 3 g of polyethylene glycol, and stirred at a stirring rate of 600 revolutions per minute for 60 minutes, and then filtered to obtain multi-layer film-coated gel particles.
[0109] In addition, the prepared multi-layer film-coated gel particles are characterized, and the results are shown in Table 1.
[0110] In addition, 30 g of the multi-layer film-coated gel particles are placed in 70 g of formation water with a salinity of 200,000 mg / L (8000 mg / L Ca 2+ 、Mg 2+ divalent salt ions, and the rest is NaCl), put into a pressure-resistant bottle and sealed. After aging at 130 °C for 60 h, the particles coalesce to form large-scale gel particle aggregates. The strength of the gel particle aggregates is 9.2 Pa.
[0111] Example 3
[0112] This example is to illustrate the preparation of multi-layer film-coated gel particles and their applications using the composition for preparing multi-layer film-coated gel particles.
[0113] The composition for preparing multi-layer film-coated gel particles includes: a gelling solution, a calcium ion-containing salt solution, and a dichloromethane solution containing a second-layer film coating agent (polylactic acid) and a dispersing aid (polyethylene glycol); wherein, the gelling solution includes preparation water, polyacrylamide, phenolic resin (hydroquinone-type phenolic resin cross-linking agent and), and a first-layer film coating agent (xanthan gum).
[0114] Among them, the relative molecular mass of polyacrylamide (AM / AMPS copolymer) is 12 million, the hydrolysis degree is 3%, the content of AM is 65% by weight, and the content of AMPS is 35% by weight;
[0115] Among them, based on the total weight of the gelling solution, the content of polyacrylamide is 0.6%; the contents of the hydroquinone-type phenolic resin cross-linking agent and the catechol-type phenolic resin cross-linking agent are 0.3% and 0.3% respectively; the content of the first-layer film coating agent xanthan gum is 0.6%; the balance is preparation water, and the content is 98.2%, and the sum of the total contents of each component is 100%.
[0116] Among them, the calcium ion-containing salt solution is calcium chloride (CaCl₂), and the concentration of calcium ions in the calcium ion-containing salt solution is 1%;
[0117] Among them, the concentration of the second-layer film coating agent polylactic acid is 20%, the concentration of polyethylene glycol is 0.3%, and the balance is dichloromethane, and the concentration of dichloromethane is 79.7%.
[0118] The method for preparing multi-layer coated gel particles using the above composition includes:
[0119] (1) At room temperature (20 ± 5 °C), add 0.6 g of AM / AMPS copolymer to clear water at a stirring rate of 600 revolutions per minute and stir for 60 minutes to obtain a polymer solution;
[0120] (2) While stirring, add 0.3 g of hydroquinone-type phenolic resin crosslinking agent and 0.3 g of catechol-type phenolic resin crosslinking agent, and stir for 10 minutes to obtain a gelling solution;
[0121] (3) While stirring, slowly add 0.6 g of xanthan gum as the first-layer coating agent, and stir for 30 minutes until it is fully dissolved to obtain a strengthened gelling solution;
[0122] (4) Then, drop the strengthened gelling solution into a 990 g aqueous solution containing 10 g of CaCl2 to obtain first-layer coated gelling solution particles;
[0123] (5) Add the first-layer coated gelling solution particles to a 797 g dichloromethane solution containing 200 g of polylactic acid and 3 g of polyethylene glycol, stir at a stirring rate of 600 revolutions per minute for 60 minutes, and filter to obtain multi-layer coated gel particles.
[0124] In addition, the prepared multi-layer coated gel particles were characterized, and the results are shown in Table 1.
[0125] In addition, 30 g of multi-layer coated gel particles were placed in 70 g of formation water with a salinity of 150,000 mg / L (6000 mg / L Ca 2+ 、Mg 2+ divalent salt ions, and the rest is NaCl), placed in a pressure-resistant bottle and sealed. After aging at 130 °C for 60 h, the particles coalesced to form large-scale gel particle aggregates. The strength of the gel particle aggregates was 7.2 Pa.
[0126] Example 4
[0127] This example is to illustrate the preparation of multi-layer coated gel particles and their applications using the composition for preparing multi-layer coated gel particles.
[0128] The composition for preparing multi-layer coated gel particles includes: a gelling solution, a calcium ion salt solution, a dichloromethane solution containing a second-layer coating agent (polylactic acid) and a dispersing aid (polyethylene glycol); wherein, the gelling solution includes prepared water, polyacrylamide, phenolic resin (phenol-type phenolic resin), and a first-layer coating agent (xanthan gum).
[0129] Among them, the polyacrylamide (AM / AMPS copolymer) has a relative molecular mass of 6 million, a hydrolysis degree of 1.8%, an AM content of 90% by weight, and an AMPS content of 10% by weight;
[0130] Among them, based on the total weight of the gelling solution, the content of polyacrylamide is 1.2%; the content of the phenol-type phenolic resin crosslinking agent is 1.0%; the content of the first-layer film-forming agent xanthan gum is 0.6%; the balance is the preparation water, with a content of 97.2%, and the sum of the total contents of each component is 100%.
[0131] Among them, the calcium ion salt solution is calcium chloride (CaCl2), and the concentration of calcium ions in the calcium ion-containing salt solution is 1%;
[0132] Among them, the concentration of the second-layer film-forming agent polylactic acid is 20%, the concentration of polyethylene glycol is 0.3%, and the balance is dichloromethane, with a concentration of 79.7%.
[0133] The method for preparing multi-layer film-coated gel particles using the above composition includes:
[0134] (1) At room temperature (20 ± 5 °C), add 1.2 g of AM / AMPS copolymer to clear water at a stirring rate of 600 revolutions per minute, and stir for 60 minutes to obtain a polymer solution;
[0135] (2) While stirring, add 1.0 g of the phenol-type phenolic resin crosslinking agent and stir for 10 minutes to obtain a gelling solution;
[0136] (3) While stirring, slowly add 0.6 g of the first-layer film-forming agent xanthan gum and stir for 30 minutes until it is fully dissolved to obtain a strengthened gelling solution;
[0137] (4) Then, drop the strengthened gelling solution into a 990 g aqueous solution containing 10 g of CaCl2 to obtain first-layer film-coated gelling solution particles;
[0138] (5) Add the first-layer film-coated gelling solution particles to a 797 g dichloromethane solution containing 200 g of polylactic acid and 3 g of polyethylene glycol, and stir at a stirring rate of 600 revolutions per minute for 60 minutes, and filter to obtain multi-layer film-coated gel particles.
[0139] In addition, the prepared multi-layer film-coated gel particles were characterized, and the results are shown in Table 1.
[0140] In addition, 50 g of multi-layer film-coated gel particles were placed in 50 g of brine with a salinity of 150,000 mg / L (6000 mg / L Ca 2+ 、Mg 2+In the formation water containing divalent salt ions (the rest being NaCl), it was placed in a pressure-resistant bottle and sealed. After aging at 110 °C for 96 h, the particles coalesced to form large-scale gel particle aggregates. The strength of the gel particle aggregates was 8.2 Pa.
[0141] Example 5
[0142] This example aims to illustrate the preparation of multi-layer coated gel particles and their applications using the composition for preparing multi-layer coated gel particles.
[0143] The composition for preparing multi-layer coated gel particles includes: a gelling solution, a calcium ion-containing salt solution, and a dichloromethane solution containing a two-layer coating agent (polylactic acid) and a dispersing aid (polyethylene glycol); among them, the gelling solution includes prepared water, polyacrylamide, phenolic resin (phenol-formaldehyde resin), and a one-layer coating agent (fructose).
[0144] Among them, the relative molecular mass of polyacrylamide (AM / AMPS copolymer) is 6 million, the hydrolysis degree is 1.8%, the content of AM is 90% by weight, and the content of AMPS is 10% by weight;
[0145] Among them, based on the total weight of the gelling solution, the content of polyacrylamide is 1.2%; the content of the phenolic resin cross-linking agent of phenol-formaldehyde type is 1.0%; the content of the one-layer coating agent fructose is 1.0%; the balance is prepared water, with a content of 96.8%, and the sum of the total contents of each component is 100%.
[0146] Among them, the calcium ion-containing salt solution is calcium chloride (CaCl2), and the concentration of calcium ions in the calcium ion-containing salt solution is 1%;
[0147] Among them, the concentration of the two-layer coating agent polylactic acid is 8%, the concentration of polyethylene glycol is 0.3%, and the balance is dichloromethane, with a concentration of 91.7%.
[0148] The method for preparing multi-layer coated gel particles using the above composition includes:
[0149] (1) At room temperature (20 ± 5 °C), 1.2 g of AM / AMPS copolymer was added to clear water at a stirring rate of 600 revolutions per minute and stirred for 60 minutes to obtain a polymer solution;
[0150] (2) While stirring, 1.0 g of the phenolic resin cross-linking agent of phenol-formaldehyde type was added and stirred for 10 minutes to obtain a gelling solution;
[0151] (3) While stirring, 1.0 g of the one-layer coating agent fructose was slowly added and stirred for 30 minutes until it was fully dissolved to obtain a strengthened gelling solution;
[0152] (4) Then, the strengthened gelling solution droplets are added to 990 g of an aqueous solution containing 10 g of CaCl2 to obtain a layer of film-coated gelling solution particles;
[0153] (5) The layer of film-coated gelling solution particles is added to 917 g of a dichloromethane solution containing 80 g of polylactic acid and 3 g of polyethylene glycol, and stirred at a stirring rate of 600 revolutions per minute for 60 minutes, and then filtered to obtain multi-layer film-coated gel particles.
[0154] In addition, the prepared multi-layer film-coated gel particles are characterized, and the results are shown in Table 1.
[0155] In addition, 50 g of the multi-layer film-coated gel particles are placed in 50 g of formation water with a salinity of 150,000 mg / L (6000 mg / L Ca 2+ 、Mg 2+ divalent salt ions, and the rest is NaCl), placed in a pressure-resistant bottle and sealed. After aging at 110 °C for 48 h, the particles coalesce to form large-scale gel particle aggregates. The strength of the gel particle aggregates is 7.9 Pa.
[0156] Example 6
[0157] This example is to illustrate the preparation of multi-layer film-coated gel particles and their applications using the composition for preparing multi-layer film-coated gel particles.
[0158] The composition for preparing multi-layer film-coated gel particles includes: a gelling solution, a calcium ion-containing salt solution, and a dichloromethane solution containing a second-layer film coating agent (polylactic acid) and a co-dispersing agent (polyethylene glycol); wherein, the gelling solution includes preparation water, polyacrylamide, phenolic resin (phenol-type phenolic resin), and a first-layer film coating agent (sodium polyacrylate).
[0159] Among them, the relative molecular mass of polyacrylamide (AM / AMPS copolymer) is 6 million, the hydrolysis degree is 1.8%, the content of AM is 90% by weight, and the content of AMPS is 10% by weight;
[0160] Among them, based on the total weight of the gelling solution, the content of polyacrylamide is 1.2%; the content of the phenol-type phenolic resin crosslinking agent is 1.0%; the content of the first-layer film coating agent sodium polyacrylate is 0.6%; the balance is preparation water, and the content is 97.2%, and the total content of each component is 100%.
[0161] Among them, the calcium ion-containing salt solution is calcium chloride (CaCl2), and the concentration of calcium ions in the calcium ion-containing salt solution is 1%;
[0162] Among them, the concentration of the second-layer film coating agent polylactic acid is 25%, the concentration of polyethylene glycol is 0.3%, and the balance is dichloromethane, and the concentration of dichloromethane is 74.7%.
[0163] The method for preparing multi-layer coated gel particles using the above-mentioned composition includes:
[0164] (1) At room temperature (20 ± 5 °C), add 1.2 g of AM / AMPS copolymer to clear water at a stirring rate of 600 revolutions per minute and stir for 60 minutes to obtain a polymer solution;
[0165] (2) While stirring, add 1.0 g of phenol-type phenolic resin crosslinking agent and stir for 10 minutes to obtain a gelling solution;
[0166] (3) While stirring, slowly add 0.6 g of the first-layer coating agent sodium polyacrylate and stir for 30 minutes until it is fully dissolved to obtain a strengthened gelling solution;
[0167] (4) Then, drop the strengthened gelling solution into a 990 g aqueous solution containing 10 g of CaCl2 to obtain first-layer coated gelling solution particles;
[0168] (5) Add the first-layer coated gelling solution particles to a 747 g dichloromethane solution containing 250 g of polylactic acid and 3 g of polyethylene glycol, stir at a stirring rate of 600 revolutions per minute for 60 minutes, and filter to obtain multi-layer coated gel particles.
[0169] In addition, the prepared multi-layer coated gel particles were characterized, and the results are shown in Table 1.
[0170] In addition, 50 g of multi-layer coated gel particles were placed in 50 g of formation water with a salinity of 150,000 mg / L (6000 mg / L of Ca 2+ , Mg 2+ divalent salt ions, and the rest is NaCl), sealed in a pressure-resistant bottle, and after aging at 110 °C for 108 h, the particles coalesced to form large-scale gel particle aggregates. The strength of the gel particle aggregates is 7.6 Pa.
[0171] Comparative Example 1
[0172] Coated gel particles were prepared according to the same method as in Example 1, except that: the first-layer coating agent was not added and the second-layer coating was not carried out to obtain a gel plugging agent, and gelation occurred at 140 °C for 3.5 hours.
[0173] In addition, the prepared gel plugging agent was characterized, and the results are shown in Table 1.
[0174] Figure 6 is the macroscopic view before and after gelation of the ordinary gel prepared in Comparative Example 1 under high temperature, high salt and formation water conditions. It can be seen from Figure 6 that when the gelling solution of the ordinary gel prepared in Comparative Example 1 first contacts the formation water, due to the density and viscosity differences, there is an obvious boundary between the gelling solution and the formation water ( Figure 6The first figure from left to right in [reference]; since both are water-based systems and there is no physical or chemical barrier, the gel-forming solution is diluted by formation water ( Figure 6 the second figure in the middle of [reference]); finally, after aging at a certain temperature, the gel strength of the gel is very low, resulting in poor plugging effect ( Figure 6 the third figure from left to right in [reference]).
[0175] Comparative Example 2
[0176] Prepare the coated gel particles according to the same method as in Example 2, the difference is that: no first-layer coating agent is added, and no second-layer coating is carried out, to obtain a gel plugging agent, which gels for 6 hours at 130 °C.
[0177] In addition, the prepared gel plugging agent was characterized, and the results are shown in Table 1.
[0178] Comparative Example 3
[0179] Prepare the coated gel particles according to the same method as in Example 3, the difference is that: no first-layer coating agent is added, and no second-layer coating is carried out, to obtain a gel plugging agent, which gels for 4 hours at 130 °C.
[0180] In addition, the prepared gel plugging agent was characterized, and the results are shown in Table 1.
[0181] Comparative Example 4
[0182] Prepare the coated gel particles according to the same method as in Example 4, the difference is that: no first-layer coating agent is added, and no second-layer coating is carried out, to obtain a gel plugging agent, which gels for 6 hours at 110 °C.
[0183] In addition, the prepared gel plugging agent was characterized, and the results are shown in Table 1.
[0184] Comparative Example 5
[0185] Prepare the gel-forming solution according to the same method as in Example 1, the difference is that: no second-layer coating is carried out, to obtain a gel particle plugging agent, and obvious coalescence occurs after aging at 140 °C for 8 hours.
[0186] In addition, the prepared gel particle plugging agent was characterized, and the results are shown in Table 1.
[0187] Comparative Example 6
[0188] Prepare the coated gel particles according to the same method as in Example 2, the difference is that: no second-layer coating is carried out, to obtain a gel particle plugging agent, and obvious coalescence occurs after aging at 130 °C for 12 hours.
[0189] In addition, the prepared gel particle plugging agent was characterized, and the results are shown in Table 1.
[0190] Comparative Example 7
[0191] The coated gel particles were prepared in the same manner as in Example 3, except that: the second layer coating was not carried out, and a gel particle plugging agent was obtained. Obvious coalescence occurred after aging at 130 °C for 12 hours.
[0192] In addition, the prepared gel particle plugging agent was characterized, and the results are shown in Table 1.
[0193] Comparative Example 8
[0194] The coated gel particles were prepared in the same manner as in Example 4, except that: the second layer coating was not carried out, and a gel particle plugging agent was obtained. Obvious coalescence occurred after aging at 110 °C for 24 hours.
[0195] In addition, the prepared gel particle plugging agent was characterized, and the results are shown in Table 1.
[0196] Comparative Example 9
[0197] The coated gel particles were prepared in the same manner as in Example 1, except that: in step (5), "polylactic acid" was replaced with "polyimide".
[0198] A gel particle plugging agent was obtained, and coalescence could not occur after aging at 130 °C for 72 hours.
[0199] In addition, the prepared gel particle plugging agent was characterized, and the results are shown in Table 1.
[0200] Comparative Example 10
[0201] The coated gel particles were prepared in the same manner as in Example 1, except that: in step (4), "990 g aqueous solution of 10 g CaCl2" was replaced with "990 g aqueous solution of 10 g MaCl2".
[0202] A gel particle plugging agent could not be obtained.
[0203] In addition, the prepared product was characterized, and the results are shown in Table 1.
[0204] Comparative Example 11
[0205] The coated gel particles were prepared in the same manner as in Example 1, except that: in step (5), "polyethylene glycol" was replaced with "sodium dodecyl sulfate".
[0206] A gel particle plugging agent was obtained, and obvious coalescence occurred after aging at 130 °C for 36 hours.
[0207] In addition, the prepared gel particle plugging agent was characterized, and the results are shown in Table 1.
[0208] Comparative Example 12
[0209] The coated gel particles were prepared in the same manner as in Example 1, except that in step (5), "200 g of polylactic acid" was replaced with "50 g of polylactic acid".
[0210] The gel particle plugging agent was obtained, and obvious coalescence occurred after aging at 130 °C for 24 hours.
[0211] In addition, the prepared gel particle plugging agent was characterized, and the results are shown in Table 1.
[0212] Table 1
[0213]
[0214] From the above results, it can be seen that the multi-layer coated gel particle plugging agent prepared by the present invention, in which one layer of coating agent in the gelling solution can rapidly crosslink with calcium ions in water to form a shaped one-layer coating, and the dense two-layer coating can protect the internal gelling solution of the gel particles from being diluted by formation water during migration. During the migration of the multi-layer coated gel particles in the formation, the gelling solution inside the particles undergoes a crosslinking reaction to form a gel under the action of high temperature. The coating protects the gelling solution from being diluted by formation water during this process. The dispersing aid in the coating improves the hydrophilicity of the gel particles, making them have good dispersibility. After migrating to the deep part of the formation, the coating gradually degrades, and the gel particles are exposed and coalesce with each other to form gel particle aggregates.
[0215] In Comparative Examples 1-4, since no one-layer coating agent was added and no two-layer coating was carried out, the gelling solution was diluted by formation water and the gelling speed was too fast, resulting in poor gelling effect and too short migration distance.
[0216] In Comparative Examples 5-8, since only one-layer coating agent was added and no two-layer coating was carried out, the formed gelling solution had good ability to resist dilution by formation water for the particles, but due to the absence of two-layer coating and dispersing aid, the particle coalescence speed was relatively fast and the migration distance could be inferred to be relatively short through the particle coalescence time.
[0217] In Comparative Example 9, since polyimide is stable at high temperature and not easily degraded, the gel particles cannot be exposed and the particles cannot agglomerate to form gel particle aggregates.
[0218] In Comparative Example 10, the one-layer coating agent has low sensitivity to magnesium ions and cannot react with magnesium ions to form a one-layer coating.
[0219] In Comparative Example 11, sodium dodecyl sulfate has a relatively low molecular weight and poor thermal stability, and rapidly degrades at high temperature and cannot stably exist on the particle surface.
[0220] In Comparative Example 12, the concentration of polylactic acid used was low, the two-layer film coating was unstable, and the degradation rate was accelerated, resulting in the faster exposure of the gel particles.
[0221] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited thereto. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solutions of the present invention, including the combination of each technical feature in any other suitable manner. These simple modifications and combinations should also be regarded as the content disclosed by the present invention and fall within the protection scope of the present invention.
Claims
1. A multi-layer coated jelly particle, characterized in that: The multi-layer coated jelly particles include a layer of coated jelly liquid particles and a second layer of coating coated on the outer surface of the first layer of coated jelly liquid particles; the second layer of coating is formed by the first layer of coated jelly liquid particles and a dichloromethane solution containing a second layer of coating agent and a dispersant, wherein the second layer of coating agent is polylactic acid and the dispersant is polyethylene glycol.
2. The multi-layer coated jelly particles according to claim 1, wherein: The coating agent is one or more of fructose, carrageenan, sodium alginate, xanthan gum, carboxymethyl cellulose, sodium carboxymethyl starch, chitosan, sodium polyacrylate and polyacrylic acid; Preferably, the coating agent is selected from one or more of fructose, carrageenan, sodium alginate, xanthan gum and sodium polyacrylate; And / or, the outer surface of the one-layer coated colloid particles is formed by a layer of coating agent and calcium ions, and the interior of the one-layer coated colloid particles is formed by polyacrylamide, phenolic resin and a layer of coating agent.
3. The multi-layer coated jelly particles according to claim 1 or 2, wherein: The thickness of the coating film is 50-500 μm; And / or, the thickness of the second coating film is 10-50 μm; And / or, the average particle size of the multi-layer coated jelly particles is 0.5 mm-10 cm.
4. A composition for preparing multi-layer coated jelly particles, characterized in that: The composition comprises a gelling solution, a salt solution containing calcium ions, and a dichloromethane solution containing a second-layer coating agent and a dispersant, which are stored independently; The gelling liquid comprises one or more of liquid preparation water, polyacrylamide, phenolic resin and a layer of coating agent; Wherein, the coating agent is one or more of fructose, carrageenan, sodium alginate, xanthan gum, carboxymethyl cellulose, sodium carboxymethyl starch, chitosan, sodium polyacrylate and polyacrylic acid; Wherein, the second layer coating agent is polylactic acid; Wherein, the dispersant is polyethylene glycol.
5. The composition according to claim 4, wherein The calcium ion-containing salt solution is one or more of calcium chloride, calcium bicarbonate and calcium hydroxide, preferably calcium chloride; and / or, the concentration of calcium ions in the calcium ion-containing salt solution is 0.5-2%; And / or, based on the total weight of the gelling solution, the content of the polyacrylamide is 0.3-1.5 weight %; the content of the phenolic resin cross-linking agent is 0.4-1.2 weight %, the content of the coating agent is 0.2-5 weight %, and the balance is liquid preparation water; And / or, the concentration of the second layer coating agent is 5-30%, the concentration of the auxiliary dispersant is 0.1-0.6%, and the balance is dichloromethane; Preferably, the concentration of the second-layer coating agent is 10%-20%, the concentration of the auxiliary dispersant is 0.2-0.3%, and the balance is dichloromethane.
6. A method for preparing multi-layer coated jelly particles using the composition according to claim 4 or 5, characterized in that: The method includes: (1) mixing the liquid preparation water and the polyacrylamide under stirring to obtain a polymer solution; (2) mixing the polymer solution with a phenolic resin for a second time to obtain a gelling solution; (3) contacting the gelling liquid with a layer of coating agent to carry out a cross-linking reaction to obtain a reinforced gelling liquid; (4) dropping the enhanced gelling liquid into a salt solution containing calcium ions to obtain a layer of coated gelling liquid particles; (5) placing the one-layer coated jelly particles into a dichloromethane solution containing a second-layer coating agent and a dispersant to obtain multi-layer coated jelly particles.
7. The method according to claim 6, wherein: The first mixing conditions include: temperature of 20±5°C, time of 60-90min, preferably 50-60min; And / or, the second mixing conditions include: temperature of 20±5°C, time of 10-20 min, preferably 10-15 min; And / or, the conditions of the cross-linking reaction include: temperature of 20±5° C., time of 20-60 min, preferably 30-50 min.
8. A multi-layer coated jelly particle prepared by the method according to claim 6 or 7.
9. Use of the multi-layer coated jelly particles according to any one of claims 1 to 3 and 8 as a plugging agent in high-temperature and high-salt fracture-cavity oil and gas reservoirs.
10. The use according to claim 9, wherein: The conditions of the high-temperature and high-salt fracture-cave oil and gas reservoir include: temperature ≥ 110°C, mineralization ≥ 200,000 mg / L, calcium and magnesium ions ≥ 5000 mg / L; Preferably, the temperature is 110-150°C, the mineralization is 200,000 mg / L-300,000 mg / L, and the content of calcium and magnesium ions is 5,000 mg / L-15,000 mg / L.
11. The use according to claim 9 or 10, wherein: The weight ratio of the multi-layer coated jelly particles to the formation water is 1:(1-9); And / or, the multi-layer coated jelly particles agglomerate to form aggregates after aging for 48-96 hours.
Citation Information
Patent Citations
Gel system suitable for profile control of high-temperature and high-salt fracture-vug type oil reservoir and application of gel system
CN113897189A
Preparation method of polyacrylamide weak gel
CN108841369A
Self-adaption fixed-point blocking composite diverting agent and application thereof
CN109796950A
Preparation method of self-assembly composite gel temporary building agent and pressure building and fracture forming method of self-assembly composite gel temporary building agent
CN116790235A
Dilution-resistant gel composition, dilution-resistant gel plugging agent and preparation method and application of dilution-resistant gel plugging agent
CN117586759A